Conexões alimentares na capitania de Goiás: 1790 a 1810 - Brito, Ana Amélia Aquino (2021)
This dissertation proposed a bibliographical study about the backlands of Goiás, having at the center of the discussion the food of its population and the medical prescriptions of the Royal Military Hospital of Vila Boa (RHMVB) in the 18th century. This chronological cut was chosen due to the fact that, in the course of investigations into the nutrition of Guayazes society, in the 18th and early 19th centuries, several documents were identified that indicated an intense flow of large shipments of products and goods to the Sertão, as well as beef, prescribed in the patients' diets and used in the food supplement of the region's residents, which aroused the interest of some governors of Goiás in the navigation trade of the Tocantinsand Araguaia rivers, trying to make a connection between Goiás and the other captaincies. These shipments, via convoys, included herbs, used sometimes as spices, sometimes asmedicine, in the RHMVB apothecary, in the treatment and cure of the sick. Such information boosted the study of the role of landings, which greatly facilitated the exchange of goods and people, the exchange of information about tax collection depots on royal roads. Thus, between 1790 and 1810, changes can be seen in all aspects of the social life of the people of the sertão, because, in the period, goods and food were transported that became part of the table of Goiás and medicine practiced in the sertão, resulting in in the incorporation of new customs to those established in the interior of the Guayazes.